A generalized Preisach approach for piezoceramic materials incorporating uniaxial compressive stress - Wolf, Felix; Sutor, Alexander; Rupitsch, Stefan; Lerch, Reinhard (Elsevier, 2012)
For various piezoceramic actuator applications, the active materials are exposed to mechanical bias stresses. Such mechanical loading strongly modifies the hysteretic transfer characteristic of the actuators. An appropriate approach to model the hysteretic characteristic is based on the Preisach operator. However, the classical Preisach model is incapable of reflecting the influence of mechanical loading. The scope of the present study is, thus, the development of a generalized Preisach model incorporating the impact of compressive stress. To accomplish this goal, the effects of stress and mechanical creep on the polarization hysteresis are characterized by means of measurements. For our model, we take advantage of an analytic Preisach distribution function, introduced in our recent work. This function is extended to a formulation incorporating uniaxial compressive bias stress. As the results clearly demonstrate, the utilized distribution function is very promising to be further extended with respect to mechanical creep behavior. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Generalized Preisach model; Analytic weight function; Stress-dependent distribution function; Uniaxial prestress; Compressive stress; PZT; Piezoceramics; Ferroelectric hysteresis; Mechanical creep